Numerical Simulation of Aqueous Humour Flow During Descemet Membrane Detachment Under External Heat Sources - Muhammad Nabil Sallehuddin; Han Nee Yong; Zuhaila Ismail; Yeou Jiann Lim; Nordin Zakaria; Maimunah Abdul Muna’aim (Spring Nature, 2026)
Indexed by Scopus